CHURCH BUILDING AND WORSHIP - Tauran, Edgar W. M.; Harwanto, Budi (Klabat Theological Review, 2024)
Worship is essential for Christians because it is an expression of the relationship between the people as creation and God as their creator. Some people assume that the act of worship is more focused on what is done in the worship service than the place where they worship. On the other hand, some argue that the place of worship is important because it affects the quality of the worship itself. This article attempts to present how the Bible provides descriptions of the relationship between worship and the place of worship from various times. A qualitative research method by investigating related literature has been conducted. The findings of this study provide that God's people have specific places of devotion and refer to one specific place that can be accessed in group devotion.  The people of God have also built proper places of worship to worship their Lord and Savior that can fulfill spiritual needs. In construction of the church building should consider the theological value of the building in revealing truth, beliefs and philosophy of the church. Keywords: worship, church building, spirituality.